Meiotic pairing in the hybrid (Zea diploperennis × Zea perennis) × Zea mays and its reciprocal - Molina, María del Carmen (2004)
Genomic formulae, fertility, chromosome pairing, and the cryptic intergenomic pairing (induced by using diluted colchicine solution) were analysed in the tri-hybrid (MDP), obtained by crossing DP40 (2n=40, which was inferred in previous studies to have originated from the fusion of an unreduced gamete of Zea diploperennis with a normal gamete of Z. perennis) with the maize inbred line Zm40 (2n=40). MDP (2n=40) showed a higher fertility (90% of the seeds are viable) than Zm40 (60%) and DP40 (80%). A regular migration of 20 chromosomes to each pole occurred in 92% of the cells in anaphase I, while bridges were observed in the other 8% of the cells. When Zm40 was used as female of the crossing (Zm40 × DP40), ears were similar to corn. Conversely, ears resembled those of the wild species when cytoplasm was donoured by Zd. Then, it can be stated the existence of cytoplasmic influence on MDP ear type. MDP had almost no I or III, with an average of 0.04I + 10.90II + 0.01III + 4.50IV. The most frequent meiotic configuration was 10II + 5IV (43.93% of the cells). On average, 33.81 chiasmata/cell were observed (17.34, 0.05 and 16.42 average numbers of chiasmata/cell in bivalents, trivalents and tetravalents, respectively). It can be inferred that the 5IV were the product of homoeologous chromosome pairing of A genomes from the three species. On the other hand, the 10II configuration suggests separate pairing of the 5 homologous B chromosomes from maize and the 5 homoeologous B chromosomes from Zp and Zd.